PENGEMBANGAN MEDIA MIBI TEMA INDAHNYA KEBERSAMAAN KELAS IV SD - Arief Hidayat Afendi; Yessi Fatima Hutasuhut; Dinda Yharsal (PGSD Universitas Muhammadiyah Cirebon, 2022)
ABSTRACT MIBI Media Development Theme for the Beauty of Togetherness for Class IV Elementary School. This thesis discusses the Development of MIBI (Miniature Indonesian Culture) Learning Media The Theme of the Beauty of Togetherness for class IV SD 066667 Medan Denai. The development model used in this study uses research and development (R & D) methods with the ADDIE development model developed by Reiser and Molenda. The steps used in this study include (Analysis-Design-Development-Implement-Evaluate). The source of the data for this research is the fourth grade students of SD 066667. The data collection technique used is using a questionnaire. The validation of the development of this learning media involves 2 validators, namely material experts and media experts. Based on the results of the study, the results of the validation of material experts obtained percentage data of 90.90% in the